MODERATE INTERPRETATION OF SHALEH DARAT IN HIS FAYḌ AL-RAḤMĀN - Ahmad Zainal Abidin; Thoriqul Aziz (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2019)
In Indonesia context, the study of Quranic Exegesis has two groups of opposite interpretations: Interpretations that are too based on the outer meaning of the text and interpretations rely more on the inner meaning of the text. Generally speaking, a balanced and moderate interpretation is an interpretation that combines the two meanings. The moderate commentators are those who do not deny the meaning of one from another. The style of interpretation of Shaleh Darat seems to combine the two meanings. This research uses descriptive-analytic method by trying to find the pattern and embodiment of moderate Interpretations in his work, Fayḍ al-Raḥmān. From the study of his work, this study found: 1) Shaleh Darat has a tendency to moderate interpretation of the Qur’an with the characteristics of fairness, balance, and tolerance. 2) His moderate interpretations appear in some verses regarding sharia and mu'amalah fields.